Effect of mulch quality on earthworm activity and nutrient supply in the humid tropics - Tian, G.; Kang, B.; Brussaard, Lijbert (Elsevier, 1997)
An experiment was conducted in 1990 and 1991 at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria to study the role of earthworms in the decomposition of plant residue mulches with different qualities. Five mulches of Dactyladenia barteri, Gliricidia sepium, Leucaena leucocephala prunings, maize (Zea mays) stover and rice (Oryza sativa) straw, which had a wide range of C-to-N ratio, lignin and polyphenol concentrations were studied. Based on their chemical compositions, Dactyladenia prunings were defined as low-quality mulch, Leucaena and Gliricidia prunings as high quality-mulches, and maize stover and rice straw as intermediate-quality mulches. The mean density of earthworms (Hyperiodrilus africanus and Eudrilus eugeniae) in the experimental plots decreased in the following order: high quality > intermediate quality > low quality mulches. High quality mulch (Leucaena and Gliricidia prunings) supported 54% higher earthworm populations than the (no mulch) control, whereas low-quality mulch (Dactyladenia prunings) only increased earthworm density by 15%, compared to the control in 1990. Plots with Leucaena and Gliricidia prunings had the highest earthworm populations at the initial stage of the experiment, while the other treatments showed increased earthworm numbers at a later stage. Effects of earthworms on mulch decomposition were examined in the field in large pots with or without earthworms (Eudrilus eugeniae). The effects of earthworms were more pronounced for Dactyladenia prunings (low quality), than for Leucaena and Gliricidia prunings (high quality). The results indicate that manipulation of earthworm activity with application of high- and low-quality mulches may improve the synchronization of soil nutrient supply and crop nutrient demand.